Meningkatkan Kemampuan Berfikir Kritis Peserta Didik Melalui Model Pembelajaran Problem Based Learning (PBL) di Kelas VII C SMPN 7 Mataram Pada Elemen Negara Kesatuan Republik Indonesia Tahun Pelajaran 2022/2023 - Hidayati, Nurul (LPPM Institut Pendidikan Nusantara Global, 2024)
This study aims to improve students' critical thinking skills through the application of the Problem Based Learning (PBL) learning model on the material about the elements of the Unitary State of the Republic of Indonesia in class VII C SMPN 7 MATARAM in the 2022/2023 academic year. The research method used is classroom action research with a cycle of planning, implementation, observation, and reflection. The subjects of this study were students of class VII C consisting of 30 students. Data were obtained through observation, written tests, interviews and documentation to measure students' critical thinking skills. The results showed that the application of the Problem Based Learning (PBL) learning model was effective in improving students' critical thinking skills. In the first cycle, only 43.33% of students reached the minimum completion criteria. However, after applying the PBL model in the second cycle, the percentage of students who reached the minimum completeness increased to 73.33%. And in the third cycle the percentage of students who reached the minimum completeness increased to 93.33%. In addition, the observation results also showed an increase in students' activities and participation during learning. Learners actively discuss, exchange opinions, and find solutions to the problems given. This shows an increase in students' critical thinking skills. Based on the results of this study, it can be a reference for teachers and other researchers who are interested in improving students' critical thinking skills through innovative learning approaches.